2020
DOI: 10.1093/humrep/deaa261
|View full text |Cite
|
Sign up to set email alerts
|

Human endometrial perivascular stem cells exhibit a limited potential to regenerate endometrium after xenotransplantation

Abstract: STUDY QUESTION What are the localization, characteristics and potential for tissue regeneration of two perivascular stem cells, namely CD34+ adventitial cells and CD146+ pericytes, in human endometrium? SUMMARY ANSWER Human endometrial CD34+ adventitial cells (located in the outermost layer of blood vessels and mainly in the basal layer) and CD146+ pericytes showed mesenchymal stem cell (MSC) phenotypes in in vitro culture, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Restructuring and maturation of the vascular network can facilitate embryo implantation [ 81 ]. Blood vessel walls are considered as stem cell-niche with a large reservoir of progenitor cells [ 82 ]. Previous study has found that eMSCs in the basalis and functionalis are mainly perivascular cells, including CD146 + and CD140b + (platelet-derived growth factor-β, PDGFR-β +) pericytes [ 50 , 51 ], sushi domain-containing-2 + (SUSD2 + ) cells [ 83 ] and CD34 + adventitial cells (located in the outermost layer of blood vessels and mainly in the basal layer) [ 82 ].…”
Section: Endometrial Stem/progenitor Cells (Enscs)mentioning
confidence: 99%
“…Restructuring and maturation of the vascular network can facilitate embryo implantation [ 81 ]. Blood vessel walls are considered as stem cell-niche with a large reservoir of progenitor cells [ 82 ]. Previous study has found that eMSCs in the basalis and functionalis are mainly perivascular cells, including CD146 + and CD140b + (platelet-derived growth factor-β, PDGFR-β +) pericytes [ 50 , 51 ], sushi domain-containing-2 + (SUSD2 + ) cells [ 83 ] and CD34 + adventitial cells (located in the outermost layer of blood vessels and mainly in the basal layer) [ 82 ].…”
Section: Endometrial Stem/progenitor Cells (Enscs)mentioning
confidence: 99%
“…Crisan et al have shown that both CD146 and PDGF-Rβ are ubiquitously expressed on pericytes surrounding endothelial cells in the capillaries of all human organs, and the co-expression of NG2 and deficient expression of endothelial markers (CD144, CD31, CD34, vWF, and UEA-1) were further confirmed by immunodetection [46]. CD146 + pericytes mainly reside in capillaries and microvessels in both the functionalis and basalis of the endometrium (Figure 2a) [47]. Moreover, higher clonogenicity was observed in CD146 + PDGF-Rβ + cells expressing SUSD2 (or W5C5), which in vivo constitute endometrial stromal tissues [48].…”
Section: Endometrial Perivascular Cells As Native Mscsmentioning
confidence: 82%
“…Interestingly, CD34 + adventitial cells express pericyte markers such as CD146, PDGFR-β, α-SMA, and NG2 after exposure to angiopoietin-2, suggesting that adventitial cells are the precursors of pericytes [57]. Recently, CD34 + CD146 − CD45 − CD56 − CD144 − adventitial cells have also been proven for the first time to exist in human endometrial tissues and are located in the outermost layer of large vessels, particularly the basal layer (Figure 2b), with an abundance nearly 40 times higher than that of pericytes [47]. Furthermore, SUSD2, another marker of perivascular cells that possesses MSC properties, is expressed mostly in the tunica media of vessels and in only a small proportion of CD34 + adventitial cells (Figure 2c).…”
Section: Perivascular Cell-based Angiogenetic Therapy For Asherman's Syndrome (As)mentioning
confidence: 95%
See 2 more Smart Citations